SUSTAINED ANTIBODY AND IMMUNOTHERAPEUTIC DELIVERY TO CERVICAL LYMPH NODES - JACKSON, Christopher; CHOI, John; PANT, Ayush; LIM, Michael; ROUTKEVITCH, Denis (2024)
Methods and compositions for treating a glioblastoma (GBM) by administering a composition comprising a hydrogel and an anti-programmed cell death protein 1 (PD-1) antibody to one or more draining lymph nodes (DLNs) of a subject in need of treatment thereof are disclosed.